A comparison of cytologic quality in fine‐needle specimens obtained with and without aspiration from superficial lymph nodes in the dog. (30th September 2021) - Karakitsou, V.; Christopher, M. M.; Meletis, E.; Kostoulas, P.; Pardali, D.; Koutinas, C. K.; Mylonakis, M. E.
Abstract : Objectives: To assess the impact of aspiration on cytologic quality of fine‐needle specimens obtained from lymph nodes of dogs and to compare the level of agreement of the cytologic diagnosis between the two sampling techniques. Materials and Methods: Fifty‐three client‐owned dogs were prospectively enrolled. Client‐owned dogs were prospectively enrolled in the study if cytologic examination of lymph nodes was indicated in the course of their clinical diagnostic work‐up. In each dog, two superficial, palpably accessible lymph nodes were sampled: one by fine‐needle aspiration and the other by fine‐needle non‐aspiration, using a 21‐Gauge needle with or without a 5‐mL syringe. Cytologic quality was assessed in duplicate smears assessed by two observers who rated cellularity, blood contamination, thickness, cell preservation and cytoplasmic fragmentation using a predefined scoring system. Results: Fifty‐three client‐owned dogs were included in the study. No significant difference was found in rating scores between the two sampling techniques for any of the cytologic quality parameters assessed. Cohen's kappa coefficient was 0.84 (95% confidence interval 0.68‐1.00), indicating diagnostic agreement between the sampling techniques. Clinical Significance: In this study, both fine‐needle aspiration and fine‐needle non‐aspiration techniques yielded lymph node specimens of comparable cytologic quality and with acceptable agreement in cytologic diagnosis.